2013
DOI: 10.3390/s130506254
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Decision Making Based Method to Adjust Automatically the Harrowing Intensity

Abstract: Harrowing is often used to reduce weed competition, generally using a constant intensity across a whole field. The efficacy of weed harrowing in wheat and barley can be optimized, if site-specific conditions of soil, weed infestation and crop growth stage are taken into account. This study aimed to develop and test an algorithm to automatically adjust the harrowing intensity by varying the tine angle and number of passes. The field variability of crop leaf cover, weed density and soil density was acquired with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…This system uses a combination of approaches for characterizing the harrowing intensity: the sensor-based mechanical weed control [ 14 , 18 ] and the measuring-controlling-regulating [ 13 ]. Both systems presented some limitations such as the use of complex and expensive sensors for plant identification (e.g., photooptic sensors, differential camera), difficult to calibrate sensors for soil density, and the “laboratory processing” required to generate the application maps, which also indicated the off-line operability.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This system uses a combination of approaches for characterizing the harrowing intensity: the sensor-based mechanical weed control [ 14 , 18 ] and the measuring-controlling-regulating [ 13 ]. Both systems presented some limitations such as the use of complex and expensive sensors for plant identification (e.g., photooptic sensors, differential camera), difficult to calibrate sensors for soil density, and the “laboratory processing” required to generate the application maps, which also indicated the off-line operability.…”
Section: Methodsmentioning
confidence: 99%
“…Variations in crop development, weed abundance, and a hard or a loose soil surface affect the harrowing performance, resulting in crop damage and variations in weed control [ 6 , 12 ]. Research during the last decade has shown that it is possible to assess variations in soil density, weed density, and crop development and automatically adjust the intensity using different approaches and prototype systems [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the recent development of site-specific mechanical weed management strategies offer the opportunity to increase the efficacy against weeds and to improve the selectivity to the crops (Melander et al, 2015;Pannacci et al, 2017). In particular, the recent automated harrowing systems designed to vary in real-time the harrowing intensity, on the basis of crop and weeds detection by sensors, have showed to increase the harrowing efficacy and balance the trade-off between crop damage and weed control (Rueda-Ayala et al, 2013). Indeed, harrowing intensity refers to the cultivation aggressiveness of the tines penetrating into the soil surface that can be varied by varying the tine angle relative to a perpendicular axis to the field surface, varying the depth of the implement, varying driving speed or through various consecutive passes on the same day of cultivation (Cirujeda et al, 2003;Rasmussen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%